Resectability after first-line FOLFIRINOX in initially unresectable locally advanced pancreatic cancer: A Single-Center Experience - Nitsche, Ulrich Peter; Michalski, Christoph (Annals of surgical oncology, 2015)
FOLFIRINOX is an active but relatively toxic chemotherapeutic regimen for patients with metastatic pancreatic ductal adenocarcinoma (PDAC). The increased frequency of responding tumors shift interest to neoadjuvant approaches. We report our institutional experience with FOLFIRINOX for therapy-naïve patients with locally advanced and initially unresectable PDAC. All patients with unresectable locally advanced PDAC who underwent treatment with FOLFIRINOX at a single center between 2011 and 2014 were identified and evaluated retrospectively regarding chemotherapy response, toxicity, conversion to resectability, and survival. Resectability, response to chemotherapy, and postoperative complications were reported according to NCCN-guidelines, RECIST-criteria, and Clavien-Dindo-classification, respectively. Overall, 14 patients received FOLFIRINOX as first-line therapy for locally advanced and unresectable PDAC. Fifty-seven percent of the patients had severe tumor-related comorbidities at the time of diagnosis, and in 86 %, dose reduction due to toxicity was necessary during a median of seven cycles. Nevertheless, only one patient had progressive disease during FOLFIRINOX, whereas the others experienced stable disease (n = 6) or partial remission (n = 6; no restaging in one patient). Oncological tumor resection was possible in 4 patients (29 % of all patients) with no postoperative mortality and only one grade 2 surgical complication. After a median follow-up of 10 months, 4 of the 14 patients were still in remission, 5 were alive with stable disease under ongoing systemic chemotherapy, and 5 died tumor-related. FOLFIRINOX is a powerful first-line regimen that leads to resectability in a substantial portion of patients with initially unresectable pancreatic cancer.